Does Competition Justify Inequality? - Björn Bartling; Manuel Grieder; Christian Zehnder (Center for Economic Studies and ifo Institute (CESifo), 2015)
Are competitive mechanisms perceived as just sources of economic inequality? Perceptions of fairness violations can have severe economic consequences, as they may cause counterproductive behavior such as rulebook slowdowns or quality shading. To analyze fairness perceptions associated with competitive mechanisms, we run laboratory experiments where a single powerful buyer can trade with one of several sellers- an environment that can lead to pronounced inequality among the interacting parties. Once the terms of trade are determined, sellers can engage in counterproductive behavior. We robustly find that low procurement prices, which allocate most of the surplus from trade to the buyer, trigger significantly less counterproductive behavior if the buyer uses a competitive auction to determine the terms of trade than if he uses his price setting power to dictate the same terms directly. Our data demonstrate that competitive mechanisms, in addition to their capability to produce efficient allocations, can reduce conflict and inefficient reactions by increasing justification for economic inequality.
Keywords: C91; D31; D63; P10; 330; fairness; competition; markets; efficiency; inequality